2015
DOI: 10.1096/fj.14-268755
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus M2 targets cystic fibrosis transmembrane conductance regulator for lysosomal degradation during viral infection

Abstract: We sought to determine the mechanisms by which influenza infection of human epithelial cells decreases cystic fibrosis transmembrane conductance regulator (CFTR) expression and function. We infected human bronchial epithelial (NHBE) cells and murine nasal epithelial (MNE) cells with various strains of influenza A virus. Influenza infection significantly reduced CFTR short circuit currents (Isc) and protein levels at 8 hours postinfection. We then infected CFTR expressing human embryonic kidney (HEK)‐293 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 55 publications
6
45
2
Order By: Relevance
“…Furthermore, this mechanism of exacerbated oxidative stress and increased production of HA provides possible treatment targets of Cl 2 -induced AHR. Post-Cl 2 -exposure treatment of human airway smooth muscle cells with an antibody against I␣I reverses the L-HA activation of RhoA (22). A previous study has shown increased level of serum urinary trypsin inhibitor, a breakdown product of I␣I in patients with RSV and suggested that this may be a marker of the severity of RSV (40).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, this mechanism of exacerbated oxidative stress and increased production of HA provides possible treatment targets of Cl 2 -induced AHR. Post-Cl 2 -exposure treatment of human airway smooth muscle cells with an antibody against I␣I reverses the L-HA activation of RhoA (22). A previous study has shown increased level of serum urinary trypsin inhibitor, a breakdown product of I␣I in patients with RSV and suggested that this may be a marker of the severity of RSV (40).…”
Section: Discussionmentioning
confidence: 94%
“…To test this hypothesis, we looked at Lys48‐ linked polyubiquitination as a proteasomal degradation signal, in both control and corrector combination‐treated conditions (55). To increase the levels of steady‐state polyubiquitinated CFTR, we inhibited the proteasome with epoxomicin (100 nM; 8 h) (56). The results demonstrated that, in control conditions, the relative polyubiquitination levels of the I507‐ATC ΔF508 CFTR were ~40% lower than those of the I507‐ATT ΔF508 CFTR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As previously described [9], cells were washed three times with PBS pH 8.0, and incubated with EZ-Link Sulfo-NHS-SS-biotin (Thermo Scientific) in PBS at pH 8.0 per manufacturer’s instructions. Cells were then incubated on ice for 15 min, and quenched three times with 50 mM Tris buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The ubiquitination and degradation of membrane proteins is well established and has been demonstrated in receptors such as the interferon alpha receptor, epidermal growth factor receptor (EGFR), Toll-like receptor 2, CFTR, Notch, E-Cadherin, etc. [912]. Of the post-translational modifications known to alter protein ubiquitination, phosphorylation is the most widely studied.…”
Section: Introductionmentioning
confidence: 99%